Multipurpose Community Centres As Focal Points For Integrated Good Governance - NGUBENI, MANDLA W. (My University, 2011)
This research report set out to develop understanding of the complex nature of the Multipurpose Community Centre (MPCC) concept. The background and initiative is grounded in the new excellence movement which seeks to have government departments and non-government agencies base their governance in the ways and methods of businesses and corporations. The study uses a qualitative purposive sample and interviews which seek to establish common understanding about the centrality of MPCCs in the development of communities. The problem statement proposes to critically investigate reasons behind the lack of commitment by various government departments to operate and provide information and service within MPCCs. The objective of this study is to identify gaps in the process of delivering government services in the MPCCs. This is aimed as an objective to help government policy makers to eliminate weaknesses in the policy governing MPCCs. Therefore in this way this study will not only sensitise the NISSC, PISSC and LISSC about the problems that government departments experience in the process of trying to establish offices and services within the MPCC but will also help the to find solutions and address problems beforehand. The chapters in the study are based on the themes as follows:, integration around delivery, integration around programmes and integration around partnerships. These chapters reveal different types activities which organizations within MPCCs can integrate. Therefore, the results show that although there is some level of integration around the themes mentioned and followed here, the integration is shallow, revealing many problems that need consideration when government establishes MPCCs. The lack of coordination of budgets, cultures and commitment have been highlighted in the conclusion as needing consideration
MM - P&DM
Keywords: Community centres; Local authorities